Decreasing sperm quality in mice subjected to chronic cannabidiol exposure: New insights of cannabidiol-mediated male reproductive toxicity - Carvalho, Renata K.; Rocha, Thiago L.; Fernandes, Fábio H.; Gonçalves, Bruno B.; Souza, Maingredy R.; Araújo, Amanda A.; Barbosa, Caio C.; Silva, Daniela M.; Campos, Hericles M.; Tomazett, Mariana V.; Ghedini, Paulo C.; Guimarães, Francisco S.; et al. (Elsevier, 2022)
Cannabidiol (CBD) is a natural cannabinoid present in the Cannabis sativa plant, widely prescribed as an anticonvulsant drug, especially for pediatric use. However, its effects on male reproduction are still little investigated. Therefore, the present study assessed the effects of CBD on the spermatogenesis and sperm quality. For this, twenty-one-day-old Swiss mice received CBD for 34 consecutive days by gavage at doses of either 15 or 30 mg/kg. Chronic exposure to CBD decreased the frequency of stages VII-VIII and XII of spermatogenesis and an increase in the frequency of stage IX were noted. Furthermore, the seminiferous epithelium height reduced at stage IX and increased at stage XII in both CBD-treated groups. There was a significant rise of sperm DNA damage, while no genotoxic effects were observed in leukocytes. The activities of superoxide dismutase and catalase decreased, while malondialdehyde levels increased in the sperm of mice treated with a higher dose of CBD. Mice exposed to 30 mg/kg of CBD showed a reduction in the mobile spermatozoa percentage and in curvilinear velocity, while straight line and average path velocity decreased in both treated groups. The number of acrosome-intact spermatozoa declined in the CBD 30 group, and the number of abnormal acrosomes raised in both CBD groups. On the other hand, the weight of reproductive organs, sperm count, and hormone levels were not affected by CBD treatment. These findings show that dysregulation of the endocannabinoid system by CBD can reduce sperm quality. The mechanisms responsible may be associated with disorders during spermatogenesis, especially during the final stages of nuclear remodelling and assembly of acrosome. However, changes in mitochondrial function, as well as the reduction on the antioxidant enzyme activities during epididymal transit, at least partly, may also be involved.
Keywords: Acrosome reaction; DNA fragmentation; Endocannabinoids; Oxidative stress; Sperm motility; Spermatogenesis